MENINGKATKAN MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DENGAN MODEL PROBLEM BASED LEARNING PADA PEMBELAJARAN IPAS UNTUK PESERTA DIDIK KELAS IV SDN 64/I MUARA BULIAN - Razaq, Abdul; Destrinelli, Destrinelli; Pamela, Issaura Sherly (Jurnal Tunas Pendidikan, 2023)
This study aims to describe the improvement of critical thinking skills with the problem-based learning model in IPAS learning for fourth grade elementary school students. This research was conducted at SDN 64/I Muara Bulian, Muara Bulian sub-district, Batanghari district, Jambi province. The form of this research is Classroom Action Research (CAR) using a qualitative approach. The research data was obtained by means of observation, interviews, and documentation. This research was conducted in two cycles, where each cycle of four stages, namely planning, implementing, observing, and reflecting. Data collection in this study was carried out through interviews, observation through observation sheets of students’ critical thinking skills, observation sheets of educator activities carrying out learning activities, and documentation. The results of this study were an increase in critical thinking skills in fourth grade students at SDN 64/I Muara Bulian after applying the problem-based learning model at each meeting in each cycle